The Effect of Using Video in Flipped Classroom Type on the Ability of SMAN 1 Bangkinang Students in Writing Recount Texts - Ayu, Sukma Sekar; Aruan, Rumiri; Syarfi, M. (Journal of Educational Sciences, 2023)
In academics, writing is a challenging skill but it is also very important to master. Based on the results of the observation at SMAN 1 Bangkinang, the writer found that students often find it difficult to write English. So this resulted in most students not being able to achieve the minimum standard of KKM in English lessons. Therefore, the use of video in flipped classroom type can be a strategy to overcome this problem. The primary aim of this pre-experimental study was to find out if there was any significant effect of using video in flipped classroom type on the ability of SMAN 1 Bangkinang students in writing recount texts. Applying a writing test consisting of pre-test and post-test in one group was used for this study. According to the findings of this study, shows that the t-test score was 6.656 while the t-table score in significance level 5% df= 23 was 2.069. Since the t-test was higher than the t-table, it can be concluded that there is a significant effect of using video in flipped classroom type on the ability of SMAN 1 Bangkinang students in writing recount texts.